Pengaruh Motivasi kerja, Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan pada PT Deco 100 Kuala Tanjung, Kabupaten Batubara, Provinsi Sumatera Utara. - Rapat Piter Sony Hutauruk; Limega Candrasa; Maria Gultom; Sri Ayu Indani (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to evaluate the influence of work motivation, work environment, and work discipline on employee performance in the context of achieving targets to increase company revenue. The issue is reinforced by the high number of customer complaints regarding discomfort experienced while shopping at the supermarket, indicating that the services provided by PT Deco 100 Kuala Tanjung, located in Batu Bara Regency, North Sumatra, do not meet consumer expectations. This has even led some customers to hesitate in becoming loyal patrons. The research adopts a quantitative approach, with data analysis conducted using the Statistical Product and Service Solutions (SPSS) software. The sample consisted of 30 employees. The analysis results show that work motivation has a negative and insignificant effect on employee performance, with a significance level of 0.281 (p > 0.05). Conversely, the work environment has a positive and significant effect on employee performance, with a significance value of 0.000 (p < 0.05). Work discipline exhibits a negative and insignificant effect on employee performance, with a t-value of 0.0148 (p < 0.05). Simultaneously, the three variables—work motivation, work environment, and work discipline—contribute 17.77% in explaining the variation in employee performance. Based on these findings, the study recommends the importance of enhancing work motivation and implementing more effective enforcement of work discipline by the company.